Formulation and characterization of tobramycin-chitosan nanoparticles coated with zinc oxide nanoparticles - Nusaiba.K. Al-nemrawi; Rami Q. Alkhatib; Hadeel Ayyad; Nid''A Alshraiedeh (Elsevier, 2022)
Herein we describe the preparation, characterization and the antibacterial effect of Tobramycin-chitosan nanoparticles (TOB-CS NPs) coated with zinc oxide nanoparticles (ZnO NPs). Four formulations of TOB-CS NPs (A-D) were prepared to study the effect of experimental variables on the NPs behavior. Two formulations of ZnO NPs were prepared using the solvothermal and the precipitation methods (ZnO1 and ZnO2), and then characterized. TOB-CS NPs (Formula d) was coated with the ZnO1. Moreover, the antibacterial activity of TOB-CS NPs, ZnO NPs and the coated nanoparticles against S. aureus and E. coli was examined. Changing the variables in preparing TOB-CS NPs resulting in variabilities in sizes (297.6-1116.3 nm), charges (+8.29-+39.00 mV), entrapment (51.95-90.60%). Further, TOB release was sustained over four days. ZnO NPs have sizes of 47.44 and 394.4 nm and charges of −62.3 and 89.4 mV when prepared by solvothermal and precipitation technique, respectively. Coated TOB-CS NPs had a size of 342 nm, a charge of +4.39 and released 100 µg/ mL of the drug after four days. The antimicrobial activity of TOB-CS NPs was lower than free TOB against S. aureus and E. coli. The coated NPs showed higher antimicrobial effect in comparison to formula D and ZnO1. In conclusion, coating TOB-CS NPs with ZnO NPs exhibited a great antibacterial effect that may be sustained for days.